2020
DOI: 10.1103/physrevlett.124.010511
|View full text |Cite
|
Sign up to set email alerts
|

Proposal for Heralded Generation and Detection of Entangled Microwave–Optical-Photon Pairs

Abstract: Quantum state transfer between microwave and optical frequencies is essential for connecting superconducting quantum circuits to coherent optical systems and extending microwave quantum networks over long distances. To build such a hybrid "quantum Internet," an important experiment in the quantum regime is to entangle microwave and optical modes. Based on the model of a generic cavity electro-optomechanical system, we present a heralded scheme to generate entangled microwave-optical photon pairs, which can byp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
82
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(83 citation statements)
references
References 107 publications
1
82
0
Order By: Relevance
“…The generated single entangled photon-phonon pairs will have applications in quantum communication and the hybrid optomechanical system can serve as quantum transducers in building hybrid quantum networks. In addition, the basic mechanism of this work can be generalized to a nondegenerate twophoton Jaynes-Cummings model [68,69], to generate entangled photon pairs with different frequency, such as entangled microwave-optical photon pairs [70].…”
Section: Discussionmentioning
confidence: 99%
“…The generated single entangled photon-phonon pairs will have applications in quantum communication and the hybrid optomechanical system can serve as quantum transducers in building hybrid quantum networks. In addition, the basic mechanism of this work can be generalized to a nondegenerate twophoton Jaynes-Cummings model [68,69], to generate entangled photon pairs with different frequency, such as entangled microwave-optical photon pairs [70].…”
Section: Discussionmentioning
confidence: 99%
“…Taking ω e = ω m , we can write down the linearized Hamiltonian of the system with rotating wave approximation [20,31]…”
Section: Piezo-optomechanical System With a Blue-detuned Drivementioning
confidence: 99%
“…Despite these encouraging * zhong.changchun@uchicago.edu † liang.jiang@uchicago.edu progress, an efficient quantum-enabled M-O transducer remains to be demonstrated, mainly due to demanding requirements of high conversion efficiency threshold and low added thermal noises. In contrast, ET doesn't require the threshold conversion efficiency, and thus is more compatible with the current technological developments [31,38,39]. A major step in ET is to demonstrate useful entanglement between microwave and optical photon pairs (or continuous modes).…”
Section: Introductionmentioning
confidence: 99%
“…Very recently it has been shown that mechanical oscillators can also be used to deterministically generate entangled electromagnetic fields [18]. Mechanical generation of microwave-optical entanglement has been proposed [19][20][21][22][23][24][25] but an experimental realization remains challenging. Low frequency mechanical transducers typically suffer from added noise and low bandwidth, while high frequency piezoelectric devices require sophisticated wave matching and new materials, which so far results in low total interaction efficiencies [26][27][28], comparable to magnon-based interfaces [29].…”
Section: Introductionmentioning
confidence: 99%